(untitled) (Nativa, 2024)
A indústria de óleos essenciais (OE) movimenta bilhões de dólares ao ano e está em plena expansão, refletindo uma crescente demanda global por aromas e fragrâncias de origem vegetal. Apesar da relevância do setor, existe uma notada falta de estatísticas detalhadas acerca da produção e comercialização de OEs, especialmente no que se refere a países em desenvolvimento. Esse estudo tem como objetivo atualizar o panorama de comercialização de OEs e a posição da indústria brasileira, utilizando os dados das bases COMEX STAT e COMTRADE. Analisaram-se as cifras anuais de importação e exportação de OEs em termos de quantidade, registradas por países (cógidos Nomenclatura Comum do Mercosul e Harmonized System iniciados em 3301), durante o período de 2012 a 2021. Destaca-se a competitividade da indústria brasileira para além dos OE de frutos cítricos, e o processamento de produtos in natura da flora brasileira em países com maior desenvolvimento tecnológico, indicando um potencial a ser explorado, de produção, processamento e exportação de OE “diferenciados”. Palavras chave: economia; produção vegetal; aromas naturais. World essential oils market and place of Brazilian industry ABSTRACT: The essential oils (EOs) industry mobilizes billions yearly. It is expanding fully and reflects a growing demand worldwide for aromas and fragrances from plant sources. Despite the sector’s relevance, there is a lack of detailed statistics about production volumes and commercialization values in developing countries. Thus, the present study aims at updating the EO’s commercialization scenario and Brazil’s position in it, using data available in the COMEX STAT and COMTRADE databases. We analyzed quantities (net kilogram) and annual values (US) of import and export of AEs registered by the countries (3301 NCM and HS codes) for the period 2012 to 2021. We present and discuss global trends by countries and by-products. We also discuss the relevance of North American and European markets to the demand for EO and India, China, and Brazil in world exports. We found the commercialization of products of Brazilian origin, distilled and processed in other countries. Therefore, this study points to an unexplored potential for the production, processing and exportation of “differentiated” EOs. Keywords: economy; crop production; natural fragrances.